Power Infrastructure and Electricity in Nigeria: Policy Considerations for Economic Welfare - Nwokoye, Ebele Stella; Dimnwobi, Stephen K.; Ekesiobi, Chukwunonso S.; Obegolu, Casmir C. (NIU Journal of Humanities, 2017)
Regular, adequate and affordable power supply, which are key indicators of improvements in economic welfare and by extension economic growth, are missing from Nigeriaâ€™s clime hence the country faces a lot of developmental challenges including the risk of losing potential investors. This paper examined power infrastructure and electricity in Nigeria using descriptive demonstrations. Tables, charts and figures were used to provide evidences which support the huge gulf between electricity produced by the various power infrastructures and electricity demand in Nigeria. Electric power production, transmission and distribution capacities of 3,600MW, 5,838MW and 8,425MVA respectively are grossly inadequate to meet power demand of 10,000MW in Nigeria. This leaves estimated power generation, transmission and distribution deficits of 6,400MW, 3,502MVA and 6,740MW respectively. This study emphasizes that the  infrastructure deficits requires about 8.1 trillion naira to finance and therefore recommends that the Nigerian government, the generating companies and the distribution companies should all make concerted efforts towards growing and developing the power infrastructure in the country. The government should also create a secure and enabling environment, free from corruption and undue interference, for the power sector to thrive and contribute positively towards improving the welfare of electricity consumers in the country. Key words: economic welfare, electricity demand, electricity supply, Nigeria, power infrastructure